Model Pembelajaran Humanistik - Arbayah, Arbayah (Dinamika Ilmu, 2013)
Humanisme views human as the free subject to determine his life. Humans are fully responsible for his own life and also for the people. Humanistic education theory in the 1970s refered to three philosophical theories namely pragmatism, progressivism and eksistensisalisme. According to humanistic theory, the purpose of learning is to humanize humans. Learning process is considered successful if the students understand their environment and themselves. Humanistic education emphasizes meaning personal of the child's existence. Learners are free to determine the purpose of education according to the needs and interest. In Islam, the meaning of humanism is to humanize humans according to the role as a vicegerent of God on earth. In this man mentions, the Qur'an uses four terms that have different meanings according to the context of the Qur'an meant, among other things: al-Basyar, Al-Nās, Banī Adam, Al-Insān.